OFF-LINE SUPERCRITICAL-FLUID EXTRACTION - HIGH-RESOLUTION GAS-CHROMATOGRAPHY APPLIED TO THE STUDY OF MORACEAE SPECIES - Vilegas, JHY; Lancas, F. M.; Vilegas, Wagner [UNESP]; Pozetti, G. L. (Wiley-Blackwell, 1993)
Supercritical fluid extraction with CO2, Performed in a home-made system, of rhizomes of Dorstenia bryoniifolia Mart. ex Miq. (Moraceae) and of bark roots of Brosimum gaudichaudii Trecul (Moraceae) afforded crude extracts that were analysed by high resolution gas chromatography (HRGC). The D. bryoniifolia extract contained, besides the previously reported pimpinelin and isobergapten, the furocoumarins psoralen, bergapten, isopimpinelin and the triterpenes alpha- and beta-amyrin and the acetate of the latter. The B. gaudichaudii extract contained a number of terpenoids as well as the previously reported psoralen and bergapten. Supercritical fluid extraction gave extracts qualitatively similar to those obtained by Soxhlet extraction with hexane and, together with off-line HRGC, was shown to be a fast and accurate technique to be used in rapid phytochemical examination.
Keywords: DORSTENIA-BRYONIIFOLIA MART EX MIQ; BROSIMUM-GAUDICHAUDII TRECUL; MORACEAE; SUPERCRITICAL FLUID EXTRACTION WITH CO2; HIGH RESOLUTION GAS CHROMATOGRAPHY